Peran Penyuluh Pertanian dalam Pembinaan Kelompok Wanita Tani (KWT) (Kasus Pengolahan Kacang Kace Canavalia pada KWT Karang Sari dan KWT Merta Sari di Desa Nyanglan, Kecamatan Banjarangkan, Kabupaten Klungkung) - SUWARNINGMAS, NI PUTU WULAN; SUARDI, I DEWA PUTU OKA; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.3, Juli 2017DO - 10.24843/JAA.2017.v06.i03.p12, 2017)
The Role of Agricultural Extension in the Development of Women Farmers Group (KWT), (A Case on Kace Canavalia Bean Processing on the KWT of Karang Sari and KWT of Merta Sari in the Village of Nyanglan, Sub-District of Banjarangkan, Regency of Klungkung Agricultural extension is a non formal education conducted by farmers to change the behavior of farmers, so that farmers become more advanced. Effective communication can support the success of agricultural extension, more importantly is to change the attitude and behavior of agricultural communities so that they learn and want to apply the information provided by Agricultural Extension. The objective of the research was to identify the roles of agricultural extension officers in the promotion of Women Farmers Group, either their role as educator, information dissemination/innovator, facilitator, consultant, supervision, monitoring and evaluation. The research was conducted in the KWT of Karang Sari and Merta Sari, the location of the study was chosen by purposive sampling. Selection of respondents was by saturated sampling method in accordance with the number of members of KWT i.e. as many as 14 people, and by using descriptive qualitative analysis method, i.e. the research aimed to provide description and explanation of the variables studied. The findings of the research showed that the role of agricultural extension in the KWT guidance, especially in the processing of Canavalia bean at KWT Karang Sari and Merta Sari has been able to play well in carrying out their duties. Revenue of KWT member of respondent is still below the Minimum Wage of Regency / City (UMK), which is Rp. 1,839,750.00 per month. This means that the extension workers are expected to foster the group of women farmers in processing Canavalia bean to have a high selling value in order to create independence and creativity of farmers in innovating to develop processed Canavalia bean products.